I have attached a picture of the question.
![I have attached a picture of the question class=](https://us-static.z-dn.net/files/dfe/1c6f38102c0daed6938034f0835f8151.jpg)
Answer:
B: 1
Step-by-step explanation:
I'm not sure what kind of given information that is, but here is my explanation:
f(x) = g(x) and values for both are given, so we combine their contents into one function: 3 - 6x = 5x - 8. Add 6x on both sides then add 8 on both sides, that'll get you 11x = 11. Divide both sides by 11 and you'll get x = 1.